Educação Social como bem público e social - Rubin-Oliveira, Marlize; Lauxen, Sirlei de Lourdes; Kieling Franco, Sergio Roberto; Passos, Aruanã Antonio dos (Cadernos Zygmunt Bauman, 2021)
Apresentação do Dossiê "Educação Social como bem público e social"